2018
DOI: 10.1128/aem.00478-18
|View full text |Cite
|
Sign up to set email alerts
|

Functional Profiling and Crystal Structures of Isothiocyanate Hydrolases Found in Gut-Associated and Plant-Pathogenic Bacteria

Abstract: Isothiocyanates (ITCs) are produced by cruciferous plants to protect them against herbivores and infection by microbes. These compounds are of particular interest due to their antimicrobial and anticarcinogenic properties. The breakdown of ITCs in nature is catalyzed by isothiocyanate hydrolase (ITCase), a novel family within the metallo-β-lactamase-fold superfamily of proteins. genes that code for ITCases are particularly widespread in insect- and plant-associated bacteria. Enzymatic characterization of seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…The ITCases belong to the MBL enzyme superfamily. Five MBL proteins of S. sclerotiorum (SS1G_12040, SS1G_11053, SS1G_01079, SS1G_14439 and SS1G_12145) were selected for further study based on their conserved domain structures and sizes 21 . The amino acid sequence identity among these five MBL proteins was lower than 15%, and a phylogenetic analysis together with MBL proteins from other closely related fungal species (and characterized ITCases from bacteria as outgroups) showed that each S. sclerotiorum candidate formed a separate cluster together with their putative homologs from related fungal species.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ITCases belong to the MBL enzyme superfamily. Five MBL proteins of S. sclerotiorum (SS1G_12040, SS1G_11053, SS1G_01079, SS1G_14439 and SS1G_12145) were selected for further study based on their conserved domain structures and sizes 21 . The amino acid sequence identity among these five MBL proteins was lower than 15%, and a phylogenetic analysis together with MBL proteins from other closely related fungal species (and characterized ITCases from bacteria as outgroups) showed that each S. sclerotiorum candidate formed a separate cluster together with their putative homologs from related fungal species.…”
Section: Resultsmentioning
confidence: 99%
“…Instead, the hydrolysis of ITCs to their corresponding amines and acetamides seems to represent a more important metabolic process. The hydrolysis of ITCs to amines had been previously described in plant pathogenic bacteria, insect gut-associated bacteria and the flea beetle, Psylliodes chrysocephala 18,19,21,22 , but not until now in fungi. Interestingly GL-producing plants themselves are also reported to generate GL-derived amines 7 , albeit via a very different pathway using mercapturic acid pathway products instead of the ITC hydrolytic pathway described in microbes 22 .…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Several Gammaproteobacteria that can detoxify phenylethyl-isothiocyanate were isolated from the guts of cabbage root fly larvae [48]. Several of these bacteria possess a saxA gene encoding for a hydrolase that can break down various plant-produced isothiocyanates [49]. Deletion of the saxA gene in one of the gut microbes, Pectobacterium carotivorum, prevented this bacterium from being able to degrade plant material [38].…”
Section: Gbcs Are Supporting Diptera To Exploit Specific Niches and Fmentioning
confidence: 99%
“…Last but not least, the root flies themselves bring along microbial communities in their guts, which may help them to overcome their host plant's chemical defenses (Welte et al, 2016). Some of these gut microbes, for example Pectobacterium spp, are also root pathogens in Brassica crops (van den Bosch et al, 2018). Taken together, it is very likely that the responses triggered by root herbivory are partly triggered by and targeted to microbial pathogens (Sellam et al, 2007).…”
Section: Genementioning
confidence: 99%